Major subpopulations of Plasmodium falciparum in sub-Saharan Africa - Amambua-Ngwa, A; Amenga-Etego, L; Kamau, E; Amato, R; Ghansah, A; Golassa, L; Randrianarivelojosia, M; Ishengoma, D; Apinjoh, T; Maïga-Ascofaré, O; Andagalu, B; Yavo, W; et al. (American Association for the Advancement of Science, 2019)
Understanding genomic variation and population structure of Plasmodium falciparum across Africa is necessary to sustain progress toward malaria elimination. Genome clustering of 2263 P. falciparum isolates from 24 malaria-endemic settings in 15 African countries identified major western, central, and eastern ancestries, plus a highly divergent Ethiopian population. Ancestry aligned to these regional blocs, overlapping with both the parasite's origin and with historical human migration. The parasite populations are interbred and shared genomic haplotypes, especially across drug resistance loci, which showed the strongest recent identity-by-descent between populations. A recent signature of selection on chromosome 12 with candidate resistance loci against artemisinin derivatives was evident in Ghana and Malawi. Such selection and the emerging substructure may affect treatment-based intervention strategies against P. falciparum malaria.